ECB4CI: an enhanced cancelable biometric system for securing critical infrastructures - Yang, Wencheng; Wang, Song; Zheng, Guanglou; Chaudhry, Junaid; Valli, Craig (The Journal of supercomputing, 2018)
Physical access control is an indispensable component of a critical infrastructure. Traditional password-based methods for access control used in the critical infrastructure security systems have limitations. With the advance of new biometric recognition technologies, security control for critical infrastructures can be improved by the use of biometrics. In this paper, we propose an enhanced cancelable biometric system, which contains two layers, a core layer and an expendable layer, to provide reliable access control for critical infrastructures. The core layer applies random projection-based non-invertible transformation to the fingerprint feature set, so as to provide template protection and revocability. The expendable layer is used to protect the transformation key, which is the main weakness contributing to attacks via record multiplicity. This improvement enhances the overall system security, and undoubtedly, this extra security is an advantage over the existing cancelable biometric systems.